Pityriasis Versicolor Resistant to Antifungal Drugs in a Patient in Lomé (Togo) - Julienne Teclessou; Koussake Kombate; Bayaki Saka; Séfako Abla Akakpo; Palokinam Pitche (Hindawi Limited, 2022)
Background. Pityriasis versicolor (PV) is a ubiquitous superficial skin mycosis that often affects young adults. It is often effectively treated with local or oral antifungal agents. Cases of PV resistance to antifungal agents have been reported rarely. We report a case of antifungal resistant PV. Observation. A 22-year-old patient was followed since the age of 17 years in a dermatology outpatient clinic for hyperpigmented scaly macular lesions of the trunk and upper limbs. The clinical diagnosis of PV was retained. The patient was treated by fluconazole 300 mg/week before being lost to follow-up. He was seen again in 2019 (about 2 years later) for the same symptomatology and treated again by fluconazole and ciclopirox olamine cream without improvement. He was again lost to follow-up and seen again six months later. A mycological sample was taken and Aspergillus niger was isolated. The patient was treated by itraconazole for 6 weeks. The evolution was marked by a clinical status quo. The patient was again put on salicylated petroleum jelly 10% associated with terbinafine cream and then lost to follow-up. Conclusion. The emergence of fungal resistance to antifungal drugs does not spare PV. It can therefore be resistant to several antifungal drugs, leaving clinicians and patients in despair.